Overview of trachoma Part 1 - Emerson, Paul (Henry Stewart Talks, 2020)
Introducing trachoma as an NTD, Individual and social consequences of trachoma, Transmission of trachoma, Clinical signs of trachoma, Global prevalence of trachoma